Prolonged Self-Resolving Neutropenia Following Asymptomatic COVID-19 Infection - Desai, Shreya (Cureus, 2021)
Multiple hematologic complications have been reported as a result of the novel coronavirus disease 2019 (COVID-19) infection. These include leukopenia, lymphopenia, thrombocytopenia as well as increased risk of venous thromboembolism. Neutropenia is a relatively uncommon finding, especially in asymptomatic patients with no other evidence of systemic infection. A young, healthy male undergoing training for the Navy was admitted with rhabdomyolysis following intense physical activity. He was incidentally noted to have severe neutropenia with the white blood cell (WBC) count of 2.1 × 10(9)/L and an absolute neutrophil count (ANC) of 355 cells/μL one month following prior asymptomatic COVID-19 infection. Further evaluation was negative for other infectious processes, nutritional deficiency, or underlying malignancy. Given young age without comorbidities and lack of febrile illness, watchful waiting was recommended in lieu of bone marrow biopsy which resulted in spontaneous resolution of neutropenia and normalization of WBC. The authors argue that although most hematologic complications of COVID-19 are reported in symptomatic patients, asymptomatic patients also appear to have a risk of developing hematologic complications including bone marrow suppression. Watchful waiting may be an appropriate diagnostic approach in such young, healthy individuals.